2015
DOI: 10.1002/cam4.584
|View full text |Cite
|
Sign up to set email alerts
|

The effect of aloe emodin–encapsulated nanoliposome‐mediated r‐caspase‐3 gene transfection and photodynamic therapy on human gastric cancer cells

Abstract: Gastric carcinoma (GC) has high incidence and mortality rates in China. Surgery and chemotherapy are the main treatments. Photodynamic therapy (PDT) has become a new treatment modality, appearing in recent experimental studies and clinical trials in various tumors. This study explores the combined effect of gene transfection with PDT on GC cells using aloe emodin (AE)–encapsulated nanoliposomes, which acted as gene carrier as well as one photosensitizer (PS). AE‐encapsulated nanoliposomes (nano‐AE) were prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“… have demonstrated that the cytoskeletal alteration was potentially involved in anoikis induced by AE‐PDT in human lung carcinoma H460 cells. Our previous study also demonstrated that AE‐PDT produced significant photocytotoxicity and induced apoptosis in tumors . However, the molecular mechanism of AE‐PDT is still not completely clear.…”
Section: Discussionmentioning
confidence: 95%
“… have demonstrated that the cytoskeletal alteration was potentially involved in anoikis induced by AE‐PDT in human lung carcinoma H460 cells. Our previous study also demonstrated that AE‐PDT produced significant photocytotoxicity and induced apoptosis in tumors . However, the molecular mechanism of AE‐PDT is still not completely clear.…”
Section: Discussionmentioning
confidence: 95%
“…Additionally, aloe‐emodin was used as a photosensitizer to explore the effect of photodynamic therapy (PDT) in human gastric cancer SGC‐7901 cells. Li et al () explored the combined effect of gene transfection with PDT on SGC‐7901 cells using aloe‐emodin‐encapsulated nanoliposomes. The results revealed that aloe‐emodin‐encapsulated nanoliposomes‐mediated r‐caspase‐3 gene transfection coupled with PDT remarkably inhibited the proliferation of SGC‐7901 cells.…”
Section: Pharmacologymentioning
confidence: 99%
“…The results revealed that aloe‐emodin‐encapsulated nanoliposomes‐mediated r‐caspase‐3 gene transfection coupled with PDT remarkably inhibited the proliferation of SGC‐7901 cells. The main mechanisms were attributed to aloe‐emodin‐induced apoptosis and necrosis of gastric cancer cells (Li et al, ). Similarly, Lin et al () also showed that aloe‐emodin‐induced PDT exerted an inhibitory effect on SGC‐7901 cells in dose‐dependent and energy‐dependent manners.…”
Section: Pharmacologymentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al investigated the effect of transfection of r-caspase-3 with nanoliposomes loaded with AE and photodynamic therapy in human gastric cancer cells [ 165 ]. Nano-AE was employed as delivery carrier for plasmid r-caspase-3 transfection, which, consequently, induced apoptosis, and also as photosensitizer for photodynamic therapy.…”
Section: Natural Products and Drug Delivery In Oncologymentioning
confidence: 99%